A Case Report of a Ganglion Cell Containing Giant Pituitary Adenoma Showing Unusual Demographic and Radiological Features - Anil Felix Angelo Fonseca; Kishore T. Vijaya; B. S. Siva Reddy; Ravi Verma (Indian Journal of Neurosurgery)
The occurrence of a ganglion cell containing pituitary adenoma is an uncommon entity. We report a rare case of a sellar mass of ganglion cell containing pituitary adenoma showing unusual demographic and radiologic features.